Women Self-Help Groups and Sustainable Development Goals: A Case Study Approach (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Self-help groups have evolved as effective grassroots tools for fostering social and economic development, particularly among marginalised groups. Poverty, financial illiteracy, a lack of education, and women’s disempowerment continue to be difficulties for rural women. Microfinance has been shown to be a transforming force in the fight against poverty, driving economic development. In India, self-help groups are at the forefront of these initiatives, as a crucial tool for empowerment and long-term change. Using a case study approach, this paper investigates the important role of SHGs in accomplishing the Sustainable Development Goals. The study examines real-world examples to demonstrate how SHGs help alleviate poverty, promote gender equality, increase financial inclusion, and empower women. This study employs a robust mixed-methods approach, combining an extensive literature review with rich qualitative insights gathered through focus group discussions and in-depth interviews. The research engages directly with women SHG leaders across six talukas of Navsari district, providing a comprehensive understanding of their experiences and the transformative impact of SHGs. The study concludes that Self-Help Groups have effectively contributed to the achievement of several Sustainable Development Goals, including SDG 1 (No Poverty), SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), SDG 10 (Reduced inequality) and, SDG 12 (Responsible Consumption & Production). It highlights the pivotal role of SHGs as key drivers of inclusive growth, emphasizing their significance in fostering a more equitable and sustainable future.